1983
DOI: 10.5558/tfc59189-4
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Spruce Plantings in Minnesota: Container vs Bareroot Stock and Fall vs Spring Planting

Abstract: RdsumdBlack spruce (Picea mariana (Mill. A~~~~~ difference significative de croissance nla the two container systems. The 2-2 stock generally percu entre les deux types de contenants. Cependant had better survival than the 3-0 stock. Survival of les plants 2-2 ant montre un taux de survie superieur fall-planted stock was equal to or better than that of aux plants 3-0. La plantation d'automne a montre un the spring-planted stock.)taux de survie egal ou superieur a la plantation de printemps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Greater initial growth for other types of container-grown seedlings was observed previously [1,9]. In the present experiment, the large containerized seedlings had higher initial nutritional status than the large bare-root stock (foliar-N concentrations of 1.64% and 1.48% for the former and the latter, respectively), as a result of their nursery cultivation regime (M. Tourigny, pers.…”
Section: Impacts Of Stock Typesupporting
confidence: 53%
See 1 more Smart Citation
“…Greater initial growth for other types of container-grown seedlings was observed previously [1,9]. In the present experiment, the large containerized seedlings had higher initial nutritional status than the large bare-root stock (foliar-N concentrations of 1.64% and 1.48% for the former and the latter, respectively), as a result of their nursery cultivation regime (M. Tourigny, pers.…”
Section: Impacts Of Stock Typesupporting
confidence: 53%
“…Planting bare-root or containerized spruce stock types could play a significant role in the success of plantation establishment [33]. These stock types generally differ in their water relations during the first few years after planting; bare-root seedlings generally experience greater planting stress than containerized seedlings [1,40]. This greater stress is attributed to the reduced root system permeability of bare-root stock, compared to containerized stock [15] and desiccation or injury to roots during planting activities [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, peat pellet produced seedlings, showed no qualitative advantage over bare-root seedlings even after several years of growth in the nursery. Alm (1983) obtained the opposite results, observing greater stress in plants grown in the ground nursery. Transplant shock was manifested by a reduction of the root system and a greater degree of damage than observed in container-grown plants.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, large seedlings can be produced either in containers or as bareroot stock. Field comparisons of containerized and bareroot seedlings are numerous (e.g., [19][20][21][22]). However, most studies have examined stock types of different initial dimensions (see [23]); few have investigated the relative performance of bareroot and containerized seedlings that are similar in size at the time of planting [24][25][26].…”
Section: International Journal Of Forestry Researchmentioning
confidence: 99%